DINAMIKA GUGAT CERAI ISTRI TERHADAP SUAMI DAN PENANGGULANGANNYA MELALUI MEDIASI BERBASIS KONSELING ISLAM FAMILY THERAPY STRUCTURAL DI PENGADILAN AGAMA - Irman Irman (Al Irsyad : Jurnal Bimbingan Konseling Islam, 2015)
This research is founded on concern toward many cases that appear because procedure of wife divorce case to husband in religion court. Procedure of case divorce is a social occurrence that is happened in society existence and every years procedure of case divorce has occurred to increase that is fantastic. One of approach that is regarded precise for controling that case is mediation that based Islam counseling with family therapy structural. This study aims to detect procedure of occurrence divorce and to know effectiveness of mediation based on Islam couseling with family therapy structural to improve positive attitude about spouse.This resarch uses mixed method desigh sequence with six subjects who is procured according  porpusive random sampling, and date analysis uses grafis analysis. This result of research is detected that (1) procedure of occurrence divorce happened because husband responsibility is low for wife, the husband make relationship with the other women, the husband has cruel attitude and bad communication with wife, (2) mediation based Islam counseling with family therapy structural has a positive impact toward spouse in a change of attitude who has involved in procedure of case divorce in religion court, and highest improving is happened in cognitive aspect.According resutl of research can be explained that mediation based Islam counseling with family therapy structural is effective to handle procedure of case divorce in religion court. This result of research can be expected as foundation doing next research about handling procedure of case divorce through the other method